Pemodelan Pneumonia Berat Menggunakan Regresi Zero Inflated Negative Binomial di Gorontalo - Novianita Achmad; Muhammad Rezky Friesta Payu; Yolanda Rahim (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
In certain cases, the response variable has an excess zero that causes overdispersion. Therefore, to overcome overdispersion because excess zero Zero-inflated negative binomial regression can be used. The purpose of this study is to apply Zero inflated negative binomial regression to model the case of severe pneumonia in Bone Bolango and on the city of Gorontalo. Based on the result of ZINB Regression, it was found that there are 3 (three) factors that are significant that is ASI, Vitamin A, and low birth weight.